(untitled) (Research, Society and Development, 2022)
The study aimed to analyze the relationship between training time and self-efficacy with self-concept and quality of life in young basketball students. The responses of 197 female and male students/athletes aged between 12 and 17 from environments where basketball is offered in the region of Curitiba, Paraná, such as schools, clubs and teaching centers of the city hall, were evaluated. High scores were found for self-concept in the domains of autonomy, finances and school, as well as in general quality of life, in relation to training time. It is concluded that there are differences from a quantitative point of view, suggesting that one can contribute to a positive perception of quality of life, self-concept and self-efficacy, which are associated with training time.